Synergy of Trademark Protection and Consumer Rights: A Legal Analysis on the Prevention of Product Counterfeiting - Hulman Panjaitan; Andrew Bethlen; Paltiada Saragi; Tomson Situmeang (Jurnal Hukum dan Keadilan, 2025)
:  This study examines legal protection for consumers in cases of product counterfeiting through the perspectives of consumer protection law and trademark law. The phenomenon of product counterfeiting is increasingly prevalent in Indonesia, causing harm not only to original producers but also endangering consumers as the most vulnerable party. This research employs a normative juridical method with a statute approach and a conceptual approach. Data sources consist of primary legal materials in the form of relevant laws and regulations, as well as secondary legal materials such as literature, journals, and expert opinions. The analysis is conducted qualitatively, emphasizing legal interpretation of applicable norms. The findings indicate that consumers are highly vulnerable in cases of product counterfeiting due to limited access to information, knowledge asymmetry, and the difficulty of distinguishing between genuine and counterfeit products. Legal protection can be pursued through two pathways: prevention and enforcement. Preventive legal strategies include strengthening regulations, integrated supervision, and consumer education. Meanwhile, enforcement is carried out through both criminal and civil legal actions against counterfeiters. Furthermore, the synergy between trademark protection and consumer protection serves as a crucial pillar in preventing counterfeiting practices, as both complement each other in ensuring justice, legal certainty, and utility. This study underscores the importance of the involvement of all stakeholders government, producers, consumers, and law enforcement authorities in establishing a layered protection system. Thus, the ultimate goal of consumer protection is not only to provide legal certainty but also to foster a fair and healthy trading environment.